Ghosts - Broomfield, Nick (United Kingdom, 2006)
On February 5th 2004 twenty three Chinese people drowned in Morecambe Bay. Their families in China are still paying off their debts. When a young girl, Ai Qin, pays $25,000 to be smuggled into the UK in order to support her family back in China, she becomes another one of 3 million migrant workers that have become the bedrock of British economy. Forced to live with eleven other Chinese people in a two bedroom house, they work in factories preparing food for British supermarkets. Risking their lives for pennies these unprotected workers end up cockling in Morcombe Bay at night. With an extraordinary debut performance from Ai Qin Lin in a film whose principal characters are played by Chinese former illegal immigrants, Ghosts offers a unique insight into a secret world that surrounds us.